Predictors of early postoperative pneumonia after oncologic surgery with the patients receiving professional oral health care: A prospective, multicentre, cohort study. Issue 7 (July 2021) - Nozaki, Shinichi; Tsutsumi, Yasuhiko; Takasaki, Yoshito; Yoshikawa, Hiromasa; Shinya, Toshiaki; Souta, Ruriko; Nakamoto, Norimichi; Marukawa, Kohei; Usami, Takeshi; Sunami, Jiro; Takashima, Maho; Tanaka, Kohji; et al.
This study was a prospective, multicentre, cohort study on 685 patients who had undergone oncologic surgery. The patients were divided into two groups according to the presence or absence of postoperative pneumonia. The two groups were compared with respect to their background, index operation, food eaten, oral condition, contents of oral care and dental treatment, laboratory data, and bacterial flora. All postoperative pneumonias occurred in six cases within four days postoperatively. The multivariable logistic regression analysis showed that preoperative serum C-reactive protein was the strongest predictor of postoperative pneumonia. In addition, decreased postoperative Candida albicans colonies was an effective predictor of postoperative pneumonia. For patients with predictors of postoperative pneumonia, perioperative strategies for its prevention should be considered in addition to professional oral health care. This study was approved by the National Hospital Organization's Central Ethics Review Board and was also approved by the directors of the participating institutions.